KOEKSISTENSI NILAI TRADISI BATANATI MASYARAKAT PULAU BURU DENGAN HUKUM ISLAM - Haryanti, Tuti; Ramsay, Sahur; Siompu, Risna (IAIN Ambon, 2025)
Batanati is a tradition of the Batujungku community on Buru Island which is carried out before a celebration. The community helps each other by handing over a sum of money to the owner of the celebration and is mandatory. This study aims to explore the substantive values ​​of the batanati tradition of the Buru Island community and its coexistence with Islamic law. This study uses empirical research using primary and secondary data. Furthermore, the data obtained is then analyzed based on the perspective of Islamic law. This study uses a conceptual and historical approach to reveal the coexistence of the substantive values ​​of the batanati tradition with Islamic law. The results of the study show that the batanati tradition is an interaction between individuals that contains local wisdom, namely the values ​​of mutual assistance, unity, togetherness and brotherhood. These values ​​become a reference and are cultivated by the community in each generation so that they become a social force. In an Islamic perspective, the batanati tradition is categorized as 'urf Sahih because it is a habit that has been carried out from generation to generation and can also be accepted and carried out by many people and does not conflict with sharia'. Therefore, the Batanati tradition needs to be maintained and the Batanati tradition continues to prioritize deliberation and consensus in order to be in line with Islamic values. Keywords: batanati tradition, islamic law, values